PENGARUH KEADILAN, NORMA EKSPEKTASI, SANKSI DAN RELIGIUSITAS TERHADAP NIAT DAN KETIDAK PATUHAN PAJAK - Yesi Mutia Basri; Raja Adri Satriawan Surya (Akuntabilitas, 2014)
This study aimed to analyze the effect of perceived tax equity, normativeexpectations (social and moral norms), legal sanctions (detection risk and penalty magnitude)and religiosity on Intention non tax compliance and non compliance behavior . In this study,Ajzen’s (1991) Theory of Planned Behavior is used as a theoretical framework to extend andcomplement tax research.The data set of the study was obtained from the survey applied to100 individual taxpayers in KPP Pratama Tampan-Pekanbaru. The results show equityperception of the tax system and moral norm have significant effect on intention but socialnorm, detection risk, penalty magnitude, and religiosity do not have effect on intention.Penalty magnitude, religiosity and intention have significant effect on non compliance behaviorDOI: 10.15408/akt.v7i3.2733